Perancangan Sistem Informasi Pengelolaan Praktikum Berbasis Website - Akbar Gunawan; Nuraida Wahyuni; Rettrikar Kiswindyatmoko; Putiri B. Katili; Dhena R. Barleany (Universitas Negeri Gorontalo, 2023)
Practicum is one of the supporting activities in the learning process as well as routine and mandatory activities that students must follow. Practicum management at the Untirta Industrial Engineering Laboratory is still carried out conventionally, so it is inflexible, inefficient, and the information provided is not detailed and transparent. The design of information systems in practicum management is carried out to overcome these problems. This study aims to obtain a practicum management information system design at the Untirta Industrial Engineering Laboratory. The method used in this study is the Framework for the Applications of System Thinking (FAST) method. The results of this study indicate that the practicum management information system design at the Untirta Industrial Engineering Laboratory is in the form of a context diagram that describes the process and scope of the system. Data flow diagrams provide an overview of data flow in processes within the system and entity relationship diagrams describe the relationships that exist in entities. Blackbox testing has been carried out on 17 page groups and shows valid results and functions properly. The usability test resulted in a system usability scale value of 86.75 which indicates that the designed information system is acceptable with grade B and an excellent rating.